Pembingkaian Berita Vonis 10 Tahun Kasus Korupsi Suap Mardani H. Maming di Media Online Tempo.co dan Suara.Com “Edisi Februari – Maret 2023” - Dwijayanti, Risqi Inayah; Baihaqi, Muhammad Asyraf; Ayu, Andina Mustika (FISIP Universitas Bung Karno, 2024)
AbstractThis research discusses the corruption case of bribery and gratuity for mining business permits (IUP) conducted by Mardani H. Maming in Tanah Bumbu Regency. The Corruption Eradication Commission (KPK) arrested Mardani H. Maming for allegedly accepting Rp. 104.3 Billion. The theory used in this study is the construction of the reality of the mass media which describes through stages and correlations, where a person does something continuously in a reality that is subjectively owned and experienced. The approach used in this study is a qualitative approach and framing analysis approach, the Constructivism paradigm, this research method is media text analysis, the nature of the research is descriptive. The use of data collection techniques in the form of documentation. The results of this study show how the media or journalists frame a news event that will be presented to the public from the perspective of the media itself, and you will see the social construction, neutrality and factulity (objectivity) of the contents of the news coverage of the two media. The conclusion of this research is that Tempo.co and Suara.com should continue to pay attention to and maintain news elements with the reporting rules stipulated in Law NO. 40 of 1999 concerning the Press and the Journalistic Code of Ethics.Keywords : News, Online Media, Framing